Experiences in Nature and Environmental Attitudes and Behaviors: Setting the Ground for Future Research - Rosa, Claudio D.; Collado, Silvia (Frontiers in Psychology, 2019)
There is empirical evidence suggesting a positive link between direct experiences in nature and people’s environmental attitudes (EA) and behaviors (EB). This has led researchers to encourage more frequent contact with nature, especially during childhood, as a way of increasing pro-environmentalism (i.e., pro-EA and pro-EB). However, the association between experiences in nature and EA/EB is complex, and specific guidelines for people’s everyday contact with nature cannot be provided. This article offers an overview of the research conducted until know about the relation between experiences in nature and pro-environmentalism, and opens up new inquiries for future research. We begin with an introduction to people’s current tendency toward an alienation from the natural world and set out the objectives of the article. It is followed by three main sections. The first one reports on what experiences in nature refer to, how and where they occur. The second section describes the different approaches used to investigate and interpret the experiences in nature-EA and EB relation. The last section provides suggestions for future research. We close by making some final remarks about the importance of (re)stablishing a greater interaction with nature for people’s pro-EA and EB.